Persepsi Konsumen Terhadap Pembelian Pangan Lokal Kupu (Studi Kasus Pada Industri Rumah Tangga Griya Jawau Melin Kelurahan Bukit Tunggal Kecamatan Jekan Raya Kota Palangka Raya) - Dina Graselita Putri; Emmy Uthanya Antang; Tri Yuliana Eka Sinta (LPPM Universitas Palangka Raya, 2021)
This study aims to: (1) to know the consumer's characteristics of local food kupu (made of cassava), and (2) to know consumer perceptions of local food kupu. This research was a case study at the Home Industry